Factors Influencing The Adoption Of Internet Of Things For Home Security In Dhaka Households - Mahmud, Arif (2023)
Globally, burglary crimes in some countries are effectively minimized by using advanced security technology supported by the Internet of Things (IoT). However, these crimes have caused rising concerns among residents in Dhaka. Despite the implementation of appropriate rules and technology development, IoT adoption in Bangladesh remains relatively low. Therefore, it is imperative to determine the factors that influence the intention to adopt IoT for home security. Accordingly, the Protection Motivation Theory (PMT) and Attitude-Social Influence-Self-Efficacy model (ASE) are integrated along with two moderating variables, personal innovativeness, and perceived trust to address the research objectives. This research implements a quantitative approach to analyze the primary data of 348 participants. Based on the findings, perceived severity, perceived vulnerability, response efficacy, response cost, and attitude are factors that impact the intention to adopt IoT with a variance of 34.9%. Moreover, the R2 and Q2 are improved respectively, due to the inclusion of personal innovativeness and perceived trust as moderators. Personal innovativeness positively moderates the relationships between response efficacy–intention, and self-efficacy–intention, and negatively moderates the attitude–intention relationship.